Aging is associated with highly defined epigenetic changes in the human epidermis - Raddatz, Günter; Hagemann, Sabine; Aran, Dvir; Söhle, Jörn; Kulkarni, Pranav P.; Kaderali, Lars; Hellman, Asaf; Winnefeld, Marc; Lyko, Frank (Epigenetics & chromatin, 2013)
Altered DNA methylation patterns represent an attractive mechanism for understanding the phenotypic changes associated with human aging. Several studies have described global and complex age-related methylation changes, but their structural and functional significance has remained largely unclear.